HUKUM ADAT LAOT (LAUT) SEBAGAI KEARIFAN MASYARAKAT NELAYAN ACEH DALAM UPAYA MELESTARIKAN POTENSI SUMBERDAYA PERIKANAN TANGKAP - - - Yulindawati (Universitas Islam Negeri Ar-Raniry, 2017)
This paper presents information on the efforts inherent in the customs of the people of Aceh to maintain the sustainability of fisheries resources is sustainable. Considering almost the bulk of the Aceh region surrounded by Sea and nearly the majority also mayasrakatnya berpropesi as fishermen make ketergantunagan to fisheries resources, especially fisheries is very high. Despite the high dependence meliki, Aceh remains meliki rules contained in the customs begaimana sustainable fishery resource management and the rule known as adat laot Hukom. Indigenous Hukom LAOT a local wisdom in the form of systems and rules that shape and mensinerjiskan common understanding among the Acehnese fishermen to exploit fishery resources in an ethical, responsible and sustainable. Moreover this wisdom capable of directing every character fishermen to act wisely in resolving problems between fishermen and has strict sanctions for the offenders. Wisdom, therefore, needs to be maintained / dilestarika from being displaced by the changing times and should be supported by all stakeholders for the task of protecting nature is not only charged on one community. Keywords: laot Customary Law, Wisdom Society and Resource Potential